Bifurcated Evolutionary Pathways in Multiplanet Systems Driven by Misaligned Protoplanetary Disks - Tao Fu; Yue Wang; Weiduo Hu (The Astrophysical Journal Letters)
Stellar obliquities, or spin–orbit angles, prevalent in exoplanet systems, can impose important constraints on their formation and evolution histories. Recent studies suggest that primordial misalignments between protoplanetary disks and stellar spin axes may significantly contribute to these obliquities, such as those frequently observed in systems hosting hot Jupiters. In this study, we demonstrate that misaligned protoplanetary disks combined with stellar oblateness drive complex dynamical evolution in planetary systems during their disk dispersal stages. Specifically, we identify bifurcated evolutionary pathways in multiplanet systems: systems with low star–disk misalignment angles ( ψ _⋆0 ) undergo smooth, adiabatic transport, producing nearly coplanar, low-obliquity configurations. In contrast, systems with high misalignment angles typically experience abrupt separatrix crossings in phase space, leading to large-amplitude libration of mutual planetary inclinations and then triggering chaotic eccentricity excitation. This libration and eccentricity excitation process can propagate outward in compact multiplanet systems, forming an excitation chain that can destabilize the entire system. The separatrix crossing arises from the dynamical bifurcation-induced effect, which occurs during disk dissipation when ${ψ }_{\star 0}\gtrsim 44\mathop{.}\limits^{^° }6$ (for one-planet systems). Our framework predicts that surviving typical compact multiplanet systems originating from misaligned disks evolve toward coplanar, low-obliquity configurations, consistent with observations of Kepler multiplanet systems. These results advance our understanding of planetary dynamics in misaligned disks and their evolutionary outcomes.